Development of a prototype automatic smart sand siever / Muhammad Fakhrul Rodzi Sahar - Sahar, Muhammad Fakhrul Rodzi (2024)
This sand filter machine is a project designed to help small and medium-sized businesses (SMEs). This machine is designed to separate coarse sand from fine sand. This equipment functions as a sieve to separate the sand. It designed this machine exclusively for small contractors, it allows to cut their labour and prevent the usage of several workers. Finally, the project proposal, "Automatic smart sand siever (ASSASI)" demonstrates that it can satisfy the objectives stated and is compatible with challenges that emerge. This project demands students look into the automatic smart sand siever and create a new one utilising cutting-edge Solidworks 2021 technology and style. It was invented the automatic smart sand siever.